The Relationship Between Individual Stress Levels and Psychological Safety Among Employees in an Automotive Components Manufacturing Company in Cikarang - Rizky Purnomo Adji Churnawan (International Journal of Psychology and Health Science, 2025)
This study examined the relationship between individual stress levels and psychological safety among employees in an automotive components manufacturing company located in Cikarang, West Java. The manufacturing environment—marked by strict production targets, rotating shifts, and high precision demands—often generates psychological strain that may influence employees’ sense of interpersonal safety at work. A quantitative, cross-sectional design was employed, involving 238 permanent employees from a large-scale automotive components manufacturer. Individual stress levels were measured using the Stress subscale of the Depression Anxiety Stress Scales-21 (DASS-21), while psychological safety was assessed using the Team Psychological Safety Scale (TPSS). Results revealed a significant negative correlation between individual stress levels and psychological safety (r = –0.46, p < .001), indicating that higher stress is associated with lower perceptions of psychological safety. The strongest association emerged in the Leader Interaction dimension (r = –0.51), followed by Peer Relationship and Team Climate. These findings support the Job Demands–Resources (JD–R) Model, suggesting that when personal and social resources are insufficient to offset high demands, employees’ psychological well-being and openness to interpersonal risk decline. Overall, the study underscores the importance of supportive leadership, open communication, and a collaborative team culture in maintaining psychological safety in high-pressure manufacturing environments.